2010
DOI: 10.1002/jrs.2837
|View full text |Cite
|
Sign up to set email alerts
|

The growth of the passive film on iron in 0.05 M NaOH studied in situ by Raman micro‐spectroscopy and electrochemical polarisation. Part I: near‐resonance enhancement of the Raman spectra of iron oxide and oxyhydroxide compounds

Abstract: Raman spectroscopy, in principle, is an excellent technique for the study of molecular species developed on metal surfaces during electrochemical investigations. However, the use of the more common laser wavelengths such as the 514.5-nm line results in spectra of less than optimal intensity, particularly for iron oxide compounds. In the present work, near-resonance enhancement of the Raman spectra was investigated for the iron oxide and iron oxyhydroxide compounds previously reported to be present in the passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(84 citation statements)
references
References 31 publications
10
68
3
Order By: Relevance
“…One can clearly see that the strength of the signal when using the red excitation line is higher than using the green line. This holds for both FeOOH phases and agrees to some extent with the findings of Nieuwoudt et al, 18 where a clear resonance enhancement was found toward the red part of the spectrum for several iron oxides and oxyhydroxides (though they found the maximum around 633 nm).…”
Section: Resultssupporting
confidence: 92%
“…One can clearly see that the strength of the signal when using the red excitation line is higher than using the green line. This holds for both FeOOH phases and agrees to some extent with the findings of Nieuwoudt et al, 18 where a clear resonance enhancement was found toward the red part of the spectrum for several iron oxides and oxyhydroxides (though they found the maximum around 633 nm).…”
Section: Resultssupporting
confidence: 92%
“…In the dark deposits on the steel surface, a power of 0.025 mW detected a series of well-defined peaks at 244, 300, 396 (the most intense), 476, 555, 682, 998, 1116 and 1309 cm À1 , indicating the presence of goethite [13,18,21,27]. This phase was transformed into modified hematite when the laser power was increased (2.5 mW), similarly to what happened in the light regions.…”
Section: Resultssupporting
confidence: 52%
“…Finally, when higher laser powers (2.5 and 5 mW) were employed, several sharp peaks typical of hematite were detected at 210 and 273 (very intense), 380, 478, 579 and 1274 cm À1 . The peak positions of this compound do not coincide exactly with those observed in other Raman spectra studies of iron corrosion products [13,18,19,21,27]. These differences may be due to the formation of ''modified hematite", which presents a structure with few changes or defects.…”
Section: Methodscontrasting
confidence: 49%
See 1 more Smart Citation
“…2b, we report the Raman spectra relating to porous layers annealed at different temperatures. For these films, even if treated at high temperatures, there is an intense peak at 658 cm −1 , which can be attributed to Fe 3 O 4 , together with the peak at 528 cm −1 [16] missing for barrier layers. The peaks at 225 and 293 cm −1 can be attributed to the A 1g and E g modes of hematite, respectively, and also in this case, the phonon overtone in the high wavelength region associated to Fe 2 O 3 is present.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 93%